2013
DOI: 10.1016/j.aap.2013.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Keeping baby safe: A randomized trial of a parent training program for infant and toddler motor vehicle injury prevention

Abstract: Motor vehicle crashes are responsible for much death and disability among infants and toddlers. This study evaluated Keeping Baby Safe In and Around the Car, a multimedia DVD designed to improve knowledge about car seat installation among parents of infants and toddlers. The randomized controlled trial was conducted with 195 parents of children aged 0–24 months. Effective car seat use was evaluated via a written knowledge quiz and car seat simulation. Results from analyses of covariance models show that postte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 16 publications
0
14
0
9
Order By: Relevance
“…Four interventions used video media/television adverts highlighting the need for child safety seats (Lewis, Ho, & Lennon, 2016;Shenoi, Saz, Jones, Ma, & Yusuf, 2010;Will, Sabo, & Porter, 2008). An educational DVD for home use led to parents being able to identify significantly more seat use errors than parents who did not view the DVD (Swartz et al, 2013). However, a short 30 second television advert did not significantly influence parent's intentions to check child safety seat restraints (Lewis, Ho, & Lennon, 2016).…”
Section: Parent Specific Educationmentioning
confidence: 85%
See 2 more Smart Citations
“…Four interventions used video media/television adverts highlighting the need for child safety seats (Lewis, Ho, & Lennon, 2016;Shenoi, Saz, Jones, Ma, & Yusuf, 2010;Will, Sabo, & Porter, 2008). An educational DVD for home use led to parents being able to identify significantly more seat use errors than parents who did not view the DVD (Swartz et al, 2013). However, a short 30 second television advert did not significantly influence parent's intentions to check child safety seat restraints (Lewis, Ho, & Lennon, 2016).…”
Section: Parent Specific Educationmentioning
confidence: 85%
“…Although the importance of involving parents in children's road safety education is often highlighted (Muir et al, 2017), there has been limited evaluation of its effectiveness. Evidence indicated that child safety seat education improved parent's knowledge of correct safety seat installation (Swartz et al, 2013), increased safety seat use (Liu, Yang, Cheng, & Li, 2016), and reduced seat misuse errors (Duchossois et al, 2008). In contrast, much less attention has been paid to the evaluation of parent education regarding pedestrian and cycling safety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we attempted to closely mirror the education that is performed at CSS inspection stations. Compared with Schwartz  et al ,16 who instructed parents to inspect two CSS installations in the back seat of a vehicle and list the errors present, we resorted to hands-on practice. Finally, we tested long-term knowledge and skills retention that demonstrated the durability of the education.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent types of injuries in the United States are fires, submersion/suffocation, falls, and poisoning (Nagaraja et al., 2005). Risk factors associated with childhood injury include parenting behavior (Schwebel & Brezausek, 2010), child health (Schwebel & Brezausek, 2009), child cognitive development (Schwebel et al., 2015), use of safety practices (Swartz et al., 2013), poverty, family size, illiteracy, single parenting, lack of control over environment, and mental health problems (Peden et al., 2008).…”
Section: Introductionmentioning
confidence: 99%